A variação ontológica de raça na modernidade: Brasil e Cabo Verde - José Carlos dos Anjos (Ciências Sociais Unisinos)
This article aims to launch some initial clues of comparative history of the race's ontological gradients in modernity. The empirical core of the analysis is double and both in the twentieth century: on the one hand, the dissolution of the category of race in the interior of Santiago Island, Cape Verde, despite the insistence of the most powerful landlords, and, on the other hand, the persistence of race in Brazil despite the insistence of the State to erase that category in the official discourses by authoritarian governments.